The effect and mechanism of mutual aid on the subjective well-being of participants under the COVID-19 pandemic - Aiping Xu; Yiwei Zhang (BMC Psychology)
Abstract The outbreak of COVID-19 led to the emergence of various forms of mutual aid. While prior research has demonstrated that mutual aid can contribute to participants’ subjective well-being, the majority of these studies are qualitative and lack clear understanding of the underlying mechanisms. Using a questionnaire survey and structural equation modeling, this study finds that mutual aid significantly enhances the subjective well-being of participants in China. Bootstrap chained mediation analysis shows that this is mainly because mutual aid not only provides material resources to participants but also helps to expand their social networks, thereby enhancing their self-esteem and self-efficacy, and ultimately improving their subjective well-being. In the chain mediation mechanism, the total effect of social network is significantly higher than that of material resources. Our study identifies social psychological mechanisms by which mutual aid acts on participant’s subjective well-being, and it has important implications for community governance.